Cabozantinib Affects Osteosarcoma Growth Through A Direct Effect On Tumor Cells and Modifications In Bone Microenvironment - Fioramonti, M. (Sci Rep, 2018)
Osteosarcoma (OS) is the most common primary malignant tumor of the bone. Due to its high heterogeneity and to survival signals from bone microenvironment, OS can resist to standard treatments, therefore novel therapies are needed. c-MET oncogene, a tyrosine-kinase receptor, plays a crucial role in OS initiation and progression. The present study aimed to evaluate the effect of c-MET inhibitor cabozantinib (CBZ) on OS both directly and through its action on bone microenvironment. We tested different doses of CBZ in in vitro models of OS alone or in co-culture with bone cells in order to reproduce OS-tumor microenvironment interactions. CBZ is able to decrease proliferation and migration of OS cells, inhibiting ERK and AKT signaling pathways. Furthermore, CBZ leads to the inhibition of the proliferation of OS cells expressing receptor activator of nuclear factor κB (RANK), due to its effect on bone microenvironment, where it causes an overproduction of osteoprotegerin and a decrease of production of RANK ligand by osteoblasts. Overall, our data demonstrate that CBZ might represent a new potential treatment against OS, affecting both OS cells and their microenvironment. In this scenario, RANK expression in OS cells could represent a predictive factor of better response to CBZ treatment.